Self-Healing Polymers Designed for Underwater Applications - Bambang Afrinaldi; Frita Yuliati; Hermawan Judawisastra; Lia A. T. W. Asri (Advances in Polymer Technology)
Polymeric materials have been employed in a wide range of applications in both dry and wet environments. When these materials suffer damage, it becomes crucial to initiate repairs in order to mitigate further losses. The use of self-healing materials emerges as a promising strategy not only to address this issue but also possess the advantage of prolonging the product’s lifespan. Nevertheless, the development of self-healing materials tailored for wet environments presents a set of obstacles and complexities. The review examines the current state of research in the field and highlights the challenges associated with developing self-healing materials that can effectively repair damage in such environments. We discuss the self-healing mechanisms and various polymers that are extensively employed in the advancement of self-healing materials. We study the progress made in the research and development of self-healing materials specifically designed for wet environments. Furthermore, it provides a summary of various applications of self-healing materials in wet environments.